2021
DOI: 10.1111/ped.14466
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative management for umbilical hernia in infants using adhesive strapping

Abstract: Background: The aim of this study was to evaluate the efficacy of adhesive strapping (AS) for umbilical hernia (UH) in infants. Methods: A retrospective review of 30 mature infants without any treatment for UH between January 2006 and December 2008 and 87 infants (42 mature and 45 premature) who were treated with AS between January 2010 and December 2014 was conducted. The rate and age of closure of UH were compared between the groups and the complications and limitations of AS were evaluated. Results: In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Two studies reported that 7.8% and 12.6% of patients discontinued AS due to skin trouble. 16 21 One study excluded two patients who could not continue AS. 5 The overall duration of AS was reported in four studies.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported that 7.8% and 12.6% of patients discontinued AS due to skin trouble. 16 21 One study excluded two patients who could not continue AS. 5 The overall duration of AS was reported in four studies.…”
Section: Resultsmentioning
confidence: 99%
“…In previous reports, 79.8%-100% of cases were found to be closed using compression therapy, and the duration of treatment was about 2 to 6 months. 2,4,5,[8][9][10][11] In this study, hernia orifice closure was achieved in 94.8% of patients, and the average treatment time was 23.6 days. The duration of treatment was considerably shorter compared with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…Compression therapy has the advantages of early closure compared with spontaneous observation 4,7,9,10 and a high rate of hernia closure 2,4,5,8–10 ; however, it has its disadvantages, such as increasing the burden of care on the guardian, including outpatient visits and bathing, and the possibility of skin damage due to compression fixation. Many facilities and reports have used cotton balls or other compression materials in addition to tape during compression therapy 2,5,6,10,11 . The compression material is spherical and may cause widening of the umbilical caliber during compression and of the umbilical caliber and fossa after closure.…”
Section: Introductionmentioning
confidence: 99%
“…Almost 60 years later, AS for UH was reassessed in Japan. Since the early 2000s, AS for UH has been positively recommended for earlier UH closure and a reduction in redundant skin of UH [ 3 ]. Additionally, a few observational studies have shown its excellent efficacy [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a few observational studies have shown its excellent efficacy [ 4 , 5 ]. Moreover, AS for UH has been approved by the Japanese health insurance system since 2014; therefore, the number of facilities performing AS for UH has been increasing in Japan [ 3 ]. However, AS has not been widely used for the treatment of UH.…”
Section: Introductionmentioning
confidence: 99%